Fit for Business
216 p. 20 illus.
Keywords: Within compulsory education, prevocational education is intended primarily to introduce participants to the world of work. This book considers curriculum design and pedagogical practice in pre-vocational education during the last two years of compulsory education. The study focuses on seven European countries (Scotland, Latvia, Poland, Hungary, Germany, Austria, Portugal) and presents an analysis of the curriculum as it relates both to knowledge-based competencies in economics and business and to self- and social competencies. It then discusses the differences between the prescribed and the enacted curriculum as identified by means of a subsequent survey of teachers. The authors conclude with a comparative assessment of each country case study, combined with supranational recommendations.